Approach to the management of gold ore tailings via its application in cement production. (1st October 2020) - Wang, Qiang; Li, Jingjing; Zhu, Xiangnan; Yao, Geng; Wu, Peng; Wang, Zhiming; Lyu, Xianjun; Hu, Shugang; Qiu, Jun; Chen, Ping; Wang, Junxiang
Abstract: A large number of gold ore tailings pose a serious threat to the ecological environment. At the same time, with the increase of cement demand, the siliceous raw material used for cement production is in short supply and its price is rising. In this study, the gold ore tailings were used a siliceous raw material for cement production. The results proved that the clinker phases of the cements produced with different addition of gold ore tailings are 3CaO·SiO2, 2CaO·SiO2, 3CaO·Al2 O3, and 4CaO·Al2 O3 ·Fe2 O3, and their hydration products are portlandite, calcium silicate hydrate, and ettringite, both of which are same as that of the cement produced without gold ore tailings. The optimum addition of gold ore tailings is 5 wt% and the calcination temperature for the cement production is 1450 °C. Furthermore, this study proved that the application of gold ore tailings in cement production can cut down the cost of siliceous raw material for cement enterprises in practice, which is also conducive to the management of gold ore tailings. Graphical abstract: Image 1 Highlights: Gold ore tailings can be used as a siliceous raw material for cement production. The cement phases are 3CaO·SiO2, 2CaO·SiO2, 3CaO·Al2 O3, and 4CaO·Al2 O3 ·Fe2 O3 . The hydration products are portlandite, calcium silicate hydrate, and ettringite. The optimum addition of gold ore tailings in cement production is 5 wt%. It's beneficial to the management of gold ore tailings and the cement production.